Family empowerment and quality of life of parents raising children with Developmental Disabilities in 78 Japanese families - Rie Wakimizu; Keiko Yamaguchi; Hiroshi Fujioka (Elsevier, 2017)
Objectives: The families of these children experience distress both at the time of diagnosis and afterward. A top priority is to understand family empowerment, family function, and family members' quality of life (QoL) and to effectively support these families in Japan. The objective of this study was to assess the actual conditions of families living with children having DDs and to explore the factors associated with family empowerment and parents' QoL. Methods: We surveyed ninety-three parents (78 mothers, 15 fathers) from 78 families which lived with children with DDs in the capital region of Japan. We assessed two main outcomes using the Japanese versions of the following instruments: Family Empowerment Scale (FES), World Health Organization Quality of Life 26 (WHOQOL26), and other six outcomes. Correlation and multiple regression analyses were conducted. Results: No medication, cooperation with child rearing, assistance from a developmental support center, solved problems related to child rearing, and higher scores in Problem Solving contributed to higher FES scores. Higher WHOQOL26 scores were related to being a full-time housewife, higher self-esteem, no developmental support, a broad emotional support network, higher scores in Problem Solving and Role Function, and lower scores in Affective Reaction and General Function. Conclusions: We revealed that family empowerment and QoL of parents rearing children with DDs in Japan were affected by various subscales of family function and other family attributes. Effective interventions for improving family empowerment and QoL should be researched in the future. Keywords: Developmental disabilities, Family empowerment, Japan, Multiple regression analysis, Quality of life, Social support